Slurry for forming electrode of non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, and method for manufacturing non-aqueous electrolyte secondary battery

By optimizing the composition and treatment method of the slurry for electrode formation, the balance problem of nonaqueous electrolyte secondary batteries between high capacity and high output characteristics is solved, the uniformity and rapid drying of the electrode active material layer are achieved, and the manufacturing efficiency and performance of the battery are improved.

CN120359625AInactive Publication Date: 2025-07-22FUJIFILM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380086077.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-12-26
Publication Date
2025-07-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The slurry for electrode formation in the conventional non-aqueous electrolyte secondary battery is difficult to balance between high capacity and high output characteristics, and it is difficult to take into account the stability of dispersion and easy dryness, resulting in the uniformity of the electrode active material layer and the battery performance.

Method used

A specific proportion of electrode active substances, conductive additives and dispersion media is used to meet a certain specific surface area, liquid absorption amount and surface free energy difference range, dispersant is added, and surface treatment is carried out to control the viscosity and dispersion of the slurry, and ensure the uniformity and rapid drying of the electrode active substance layer.

Benefits of technology

The uniformity and smoothness of the electrode active material layer are achieved, the manufacturing adaptability and performance of the battery are improved, the drying time is shortened, and the high capacity and high output characteristics of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120359625A_ABST
    Figure CN120359625A_ABST
Patent Text Reader

Abstract

The present invention provides: a slurry for forming an electrode of a non-aqueous electrolyte secondary battery, which contains an electrode active material, a conductive auxiliary agent and a dispersion medium and satisfies formulae (1) to (4); a non-aqueous electrolyte secondary battery obtained using the slurry; and a method for manufacturing the non-aqueous electrolyte secondary battery. Formula (1) 0 < y-x < = 10, Formula (2) 0 < = x < = 30, Formula (3) SBET > = 170, and Formula (4) [Delta] E < = 30, where x is the liquid absorption amount (mL) of the dispersion medium per 100 g of the total amount of the electrode active material and the conductive auxiliary agent, y is the amount (mL) of the dispersion medium per 100 g of the total amount of the electrode active material and the conductive auxiliary agent, SBET is the BET specific surface area (m2 / g) of the conductive auxiliary agent, and [Delta] E < = 30. [Delta] E is the absolute value (mN / m) of the difference between the surface free energy of the dispersion medium and the surface free energy of the conductive auxiliary agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a paste for forming an electrode of a non-aqueous electrolyte secondary battery, a non-aqueous electrolyte secondary battery, and a method for manufacturing a non-aqueous electrolyte secondary battery. Background Art

[0002] Non-aqueous electrolyte secondary batteries represented by lithium ion secondary batteries have a high energy density, excellent storage performance, low-temperature operability, etc., and are widely used in portable electronic devices such as mobile phones and laptop computers. Further, the battery can be enlarged and used in transportation equipment such as automobiles, and is also used as a storage device for night power, power generated from natural energy, etc.

[0003] A general method for manufacturing a non-aqueous electrolyte secondary battery will be described. First, a positive electrode composed of a laminated structure of a positive electrode current collector and a positive electrode active material layer and a negative electrode composed of a laminated structure of a negative electrode current collector and a negative electrode active material layer are arranged such that the positive electrode active material layer and the negative electrode active material layer face each other with a separator interposed therebetween, thereby obtaining an electrode laminate. Usually, the electrode laminate is further wound to obtain a wound electrode body, and the wound electrode body is stored in a battery case or the like. Next, an electrolytic solution is injected into the battery case, and the electrolytic solution is permeated through the entire positive electrode active material layer, separator, and negative electrode active material layer. Then, the obtained battery is charged and discharged (initialized) to form an SEI (Solid Electrolyte Interface) on the negative electrode, thereby obtaining a non-aqueous electrolyte secondary battery. In the following description, the positive electrode and the negative electrode may be collectively referred to as "electrodes", the positive electrode active material and the negative electrode active material may be collectively referred to as "electrode active materials" or simply "active materials", and the positive electrode current collector and the negative electrode current collector may be collectively referred to as "electrode current collectors" or simply "current collectors".

[0004] Techniques for increasing the capacity of non-aqueous electrolyte secondary batteries are being studied. For example, Patent Document 1 discloses a technique in which an electrode active material layer functions as a secondary battery in a state of a paste containing a high content of an active material. Specifically, an electrochemical cell is described, which includes:

[0005] a positive electrode containing a first active material and an electrolytic solution in a first non-aqueous liquid electrolyte and composed of a non-adhesive body;

[0006] a negative electrode containing a second active material and an electrolytic solution in a second non-aqueous liquid electrolyte and composed of a non-adhesive body; and

[0007] an ion permeable membrane disposed between the positive electrode and the negative electrode, wherein,

[0008] The above-mentioned positive electrode and the above-mentioned negative electrode each have a thickness of about 200 μm to about 3000 μm.

[0009] According to the technology described in Patent Document 1, like the above-mentioned positive electrode and negative electrode, since the electrode active material layers (positive electrode active material layer and negative electrode active material layer) contain an electrolyte and are in a slurry state and non-bonded state, a thick film can be formed while maintaining the flexibility of the electrode active material layer, and an adhesive for bonding between solid particles is not required. Also, the charge capacity and overall energy density can be significantly increased while maintaining the flexibility of the battery. In the following description, as described in Patent Document 1, a non-aqueous electrolyte secondary battery obtained by forming the electrode active material layer into a slurry state containing an electrolytic solution is sometimes referred to as a quasi-solid-state secondary battery.

[0010] Prior Art Documents

[0011] Patent Documents

[0012] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2017-147222 Summary of the Invention

[0013] Technical Problem to be Solved by the Invention

[0014] In the manufacturing process of a general non-aqueous electrolyte secondary battery that is not a quasi-solid-state secondary battery, the electrode active material layer is usually formed by coating a slurry containing an electrode active material and a conductive assistant (slurry for electrode formation) on an electrode current collector and drying it. At this time, in order to improve the manufacturing efficiency, it is necessary to control the characteristics of the slurry for electrode formation from various aspects. For example, in order to improve the operability of the slurry for electrode formation and form the electrode active material layer uniformly and with high precision, it is required that the slurry for electrode formation exhibits an appropriate low viscosity and can maintain a stable dispersion state (dispersion stability) of the solid particles (active material and conductive assistant) contained therein. Also, in order to shorten the manufacturing time, it is required that the slurry for electrode formation can be quickly dried after coating (easy drying property).

[0015] From the viewpoint of easy drying property, it can be considered to reduce the amount of solvent in the slurry for electrode formation and coat a slurry with a high solid component concentration (total amount of the respective contents of the active material and the conductive assistant). However, if the solid component concentration in the electrode slurry increases, the viscosity of the slurry rises, agglomeration easily occurs, the dispersion stability decreases, and the coating adaptability deteriorates. As a result, the uniformity of the obtained electrode active material layer is impaired, the surface becomes rough, and performance deviations are likely to occur between the obtained batteries.

[0016] Moreover, in order to increase the capacity (energy density) of non-aqueous electrolyte secondary batteries, attempts have been made to use active materials containing a higher content of storage ions, and conversely, to reduce the content of conductive aids. However, as long as the content of conductive aids is reduced, the conductivity decreases, which is disadvantageous for output characteristics. Attempts have been made to achieve both increased capacity and high output characteristics by using a small amount of conductive aids with a high specific surface area that can easily form an electron conduction network. However, conductive aids with a high specific surface area cause aggregation of solid particles in the slurry, making it more difficult to ensure dispersion stability.

[0017] Furthermore, when considering the slurry for forming an electrode in the production of a quasi-solid-state secondary battery, from another perspective in addition to the above viewpoints, it is necessary to increase the concentration of the active material in the slurry for forming an electrode. That is, in a quasi-solid-state secondary battery, the slurry for forming an electrode actually functions directly as the electrode active material layer. Therefore, in the production of a quasi-solid-state secondary battery, the content of the active material in the slurry for forming an electrode is an important technical requirement directly related to increasing the capacity (energy density) of the battery. However, as described above, if the content of the active material is increased and the solid component concentration rises, the coating adaptability deteriorates. Also, as described above, if the content of the active material is further increased and a small amount of conductive aids with a high specific surface area is used, the dispersion stability will also be lost.

[0018] An object of the present invention is to provide a slurry for forming an electrode for a non-aqueous electrolyte secondary battery, which can obtain a non-aqueous electrolyte secondary battery with excellent production adaptability (dispersion stability, easy drying property, and coating adaptability) and excellent battery performance while using a conductive aid with a specified high specific surface area. Another object of the present invention is to provide a non-aqueous electrolyte secondary battery obtained by using this slurry for forming an electrode and a method for manufacturing the same.

[0019] Means for Solving the Technical Problem

[0020] The above object of the present invention is solved by the following method.

[0021] 〔1〕

[0022] A slurry for forming an electrode for a non-aqueous electrolyte secondary battery, which contains an electrode active material, a conductive aid, and a dispersion medium, and satisfies the following formulas (1) to (4).

[0023] Formula (1): 0 < y - x ≤ 10

[0024] Formula (2): 0 ≤ x ≤ 30

[0025] Formula (3): S BET ≥170

[0026] Equation (4) ΔE ≤ 30

[0027] In the above-described paste for forming an electrode, x is the liquid absorption amount (mL) of the above-described dispersion medium in the total amount of the above-described electrode active material and the above-described conductive assistant per 100 g, and can be calculated by the following Equation (5).

[0028] In the above-described paste for forming an electrode, y is the amount (mL) of the above-described dispersion medium in the total amount of the above-described electrode active material and the above-described conductive assistant per 100 g.

[0029] S BET is the BET specific surface area (m 2 / g) of the above-described conductive assistant.

[0030] ΔE is the absolute value (mN / m) of the difference between the surface free energy of the above-described dispersion medium and the surface free energy of the above-described conductive assistant.

[0031] Equation (5) x = [Sa × da / 100] + [Sc × dc / 100]

[0032] Sa is the liquid absorption amount (mL) of the above-described dispersion medium in the above-described electrode active material per 100 g.

[0033] da is the proportion (mass %) of the above-described electrode active material in the total amount of the above-described electrode active material and the above-described conductive assistant in the above-described paste for forming an electrode.

[0034] Sc is the liquid absorption amount (mL) of the above-described dispersion medium in the above-described conductive assistant per 100 g.

[0035] dc is the proportion (mass %) of the above-described conductive assistant in the total amount of the above-described electrode active material and the above-described conductive assistant in the above-described paste for forming an electrode.

[0036] 〔2〕

[0037] The paste for forming an electrode according to 〔1〕 contains an electrolyte.

[0038] 〔3〕

[0039] The paste for forming an electrode according to 〔1〕 or 〔2〕, wherein

[0040] the above Equation (2) satisfies the following Equation (2a).

[0041] Equation (2a) 0 ≤ x ≤ 21

[0042] 〔4〕

[0043] The paste for forming an electrode according to any one of 〔1〕 to 〔3〕, wherein

[0044] The above formula (4) satisfies the following formula (4a).

[0045] Formula (4a) ΔE ≤ 25

[0046] 〔5〕

[0047] The paste for forming an electrode according to any one of 〔1〕 to 〔4〕, wherein

[0048] The surface free energy of the above dispersion medium is 20 to 40 mN / m.

[0049] 〔6〕

[0050] The paste for forming an electrode according to any one of 〔1〕 to 〔5〕, wherein

[0051] The above Sa is 10 to 21 mL.

[0052] 〔7〕

[0053] The paste for forming an electrode according to any one of 〔1〕 to 〔6〕, wherein

[0054] The above Sc is 200 to 1700 mL.

[0055] 〔8〕

[0056] The paste for forming an electrode according to any one of 〔1〕 to 〔7〕, wherein

[0057] The bulk density of the above conductive aid is 35 g / L or less.

[0058] 〔9〕

[0059] The paste for forming an electrode according to any one of 〔1〕 to 〔8〕, wherein

[0060] The above conductive aid has been surface-treated.

[0061] 〔10〕

[0062] The paste for forming an electrode according to any one of 〔1〕 to 〔9〕 contains a dispersant.

[0063] 〔11〕

[0064] The paste for forming an electrode according to any one of 〔1〕 to 〔10〕, wherein

[0065] The content of the above electrode active material is 45% by mass or more.

[0066] 〔12〕

[0067] The paste for forming an electrode according to any one of 〔1〕 to 〔11〕, wherein

[0068] The content of the solid component exceeds 60% by mass.

[0069] 〔13〕

[0070] The electrode-forming paste according to any one of 〔1〕 to 〔12〕, wherein

[0071] The above electrode active material is a positive electrode active material.

[0072] 〔14〕

[0073] The electrode-forming paste according to any one of 〔1〕 to 〔13〕, wherein

[0074] The proportion da of the above electrode active material is 90.00 to 99.99% by mass, and the proportion dc of the above conductive assistant is 0.01 to 10.00% by mass.

[0075] 〔15〕

[0076] A non-aqueous electrolyte secondary battery having a positive electrode, a separator, and a negative electrode in this order, and using the electrode-forming paste according to 〔2〕 as the positive electrode active material layer and / or the negative electrode active material layer.

[0077] 〔16〕

[0078] A method for manufacturing a non-aqueous electrolyte secondary battery, comprising the following steps:

[0079] Coating the electrode-forming paste according to any one of 〔1〕 to 〔14〕 on an electrode current collector to form an electrode active material layer.

[0080] In the description of the present invention, the numerical range represented by "~" means a range including the numerical values described before and after "~" as the lower limit value and the upper limit value.

[0081] In the present invention, "non-aqueous electrolyte" means an electrolytic solution substantially free of water. That is, the "non-aqueous electrolyte" may contain a trace amount of water within a range that does not impair the effects of the present invention. In the present invention, the water concentration in the "non-aqueous electrolyte" is 200 ppm (mass basis) or less, preferably 100 ppm or less, more preferably 20 ppm or less. In addition, it is actually very difficult for the non-aqueous electrolyte to be completely water-free and usually contains more than 1 ppm of water.

[0082] In the present invention, the "non-aqueous solvent" also means a solvent that substantially does not contain water. That is, the "non-aqueous solvent" may contain a trace amount of water within the range that does not impair the effects of the present invention. In the present invention, the water concentration in the "non-aqueous solvent" is 200 ppm (mass basis) or less, preferably 100 ppm or less, more preferably 20 ppm or less. In addition, it is actually very difficult for the non-aqueous solvent to be completely water-free, and it usually contains 1 ppm or more of water.

[0083] Advantages of the Invention

[0084] The paste for forming an electrode of the non-aqueous electrolyte secondary battery of the present invention can maintain a dispersed state even after a period of time and can be dried quickly. Furthermore, a uniform coating layer can be formed. As a result, the manufacturing adaptability of the non-aqueous electrolyte secondary battery is excellent, and thus the performance of the obtained non-aqueous electrolyte secondary battery can be more excellent. In the non-aqueous electrolyte secondary battery of the present invention, in the process of forming the electrode active material layer during the manufacture of the non-aqueous electrolyte secondary battery, the drying time can be shortened, and a smooth electrode active material layer can be formed. The manufacturing adaptability is high, and the battery performance is also excellent. According to the manufacturing method of the non-aqueous electrolyte secondary battery of the present invention, in the process of forming the electrode active material layer, the drying time can be shortened, and a smooth electrode active material layer can be formed, so that a non-aqueous electrolyte secondary battery with high manufacturing adaptability and excellent battery performance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Figure 1 It is a longitudinal sectional view schematically showing a basic laminated structure of an embodiment of the secondary battery according to the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0086] Preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments except as specified in the present invention.

[0087] [Paste for Electrode Formation]

[0088] The paste for forming an electrode of the present invention (also referred to as "the paste of the present invention") is a paste containing an electrode active material, a conductive additive, and a dispersion medium, and is a paste suitable for forming an electrode active material layer of a non-aqueous electrolyte secondary battery.

[0089] The electrode active material can be a positive electrode active material or a negative electrode active material, and a positive electrode active material is more preferred. When the paste of the present invention contains a positive electrode active material, the paste of the present invention can be used as a paste for forming a positive electrode active material layer. When the paste of the present invention contains a negative electrode active material, the paste of the present invention can be used as a paste for forming a negative electrode active material layer.

[0090] In a preferred embodiment (the first embodiment) of the paste of the present invention, the paste of the present invention is used as a paste for forming an electrode of a general non-aqueous electrolyte secondary battery (a non-aqueous electrolyte secondary battery that is not a quasi-solid state secondary battery). Further, in another preferred embodiment (the second embodiment) of the present invention, the paste of the present invention is used as a paste for forming an electrode of a quasi-solid state secondary battery. The paste for forming an electrode in the second embodiment contains an electrolyte (that is, an electrolytic solution obtained by adding an electrolyte to a dispersion medium), which is different from the first embodiment.

[0091] The paste of the present invention satisfies the following formulas (1) to (4).

[0092] Formula (1): 0 < y - x ≤ 10

[0093] Formula (2): 0 ≤ x ≤ 30

[0094] Formula (3): S BET ≥170

[0095] Formula (4): ΔE ≤ 30

[0096] In the above paste for forming an electrode, x is the liquid absorption amount (mL) of the dispersion medium in the total amount of the above electrode active material and the above conductive assistant per 100 g, and can be calculated by the following formula (5).

[0097] In the above paste for forming an electrode, y is the amount (mL) of the dispersion medium in the total amount of the above electrode active material and the above conductive assistant per 100 g.

[0098] S BET is the BET specific surface area (m 2 / g) of the above conductive assistant.

[0099] ΔE is the absolute value (mN / m) of the difference between the surface free energy of the above dispersion medium and the surface free energy of the above conductive assistant.

[0100] Formula (5): x = [Sa × da / 100] + [Sc × dc / 100]

[0101] Sa is the liquid absorption amount (mL) of the dispersion medium in the above electrode active material per 100 g.

[0102] da is the proportion (mass %) of the above electrode active material in the total amount of the above electrode active material and the above conductive assistant in the above paste for forming an electrode.

[0103] Sc is the liquid absorption amount (mL) of the dispersion medium in the above conductive assistant per 100 g.

[0104] dc is the proportion (mass %) of the conductive additive in the total amount of the electrode active material and the conductive additive in the above-mentioned slurry for forming an electrode.

[0105] The slurry of the present invention satisfies the formula (1) 0 < y - x ≤ 10. That is, in the slurry of the present invention, according to the liquid absorption amount x (mL) of the dispersion medium in every 100 g of the total amount of the electrode active material and the conductive additive constituting the slurry, the amount y (mL) of the dispersion medium in every 100 g of the total amount of the electrode active material and the conductive additive is controlled within a specified range. In the present invention, y - x is sometimes referred to as the effective liquid amount.

[0106] Among them, in the present invention, the "liquid absorption amount of the dispersion medium in every 100 g of the total amount of the electrode active material and the conductive additive" means the amount of the dispersion medium that can be retained in the structure of 100 g of a mixture obtained by mixing the electrode active material types and the conductive additive types present in the same content ratio as in the slurry.

[0107] x can be obtained by the formula (5). In the formula (5), the method for determining the liquid absorption amount Sa of the dispersion medium in every 100 g of the electrode active material and the liquid absorption amount Sc of the dispersion medium in every 100 g of the conductive additive will be described later.

[0108] If the above-mentioned liquid absorption amount x is too small with respect to the amount y of the dispersion medium (y - x > 10), then when coating the slurry to form an electrode active material layer, and then during drying, the amount of the solvent to be volatilized becomes large and voids and the like are likely to be generated in the electrode active material layer. As a result, the volume energy density decreases. Also, when coating the slurry to form an electrode active material layer, an excessive amount of the dispersion medium flows out from the end, which also causes a decrease in the smoothness of the electrode active material layer.

[0109] Regarding the formula (1), the slurry of the present invention preferably satisfies the following formula (1a), more preferably satisfies the following formula (1b), still more preferably satisfies the following formula (1c), and further preferably satisfies the following formula (1d).

[0110] Formula (1a) 1.0 ≤ y - x ≤ 10

[0111] Formula (1b) 3.0 ≤ y - x ≤ 10

[0112] Formula (1c) 6.0 ≤ y - x ≤ 10

[0113] Formula (1d) 7.0 ≤ y - x ≤ 9.0

[0114] In the slurry of the present invention, the liquid absorption amount x of the dispersion medium in the total amount of 100 g of the electrode active material and the conductive assistant satisfies the formula (2): 0 ≤ x ≤ 30. That is, the total liquid absorption amount of the electrode active material and the conductive assistant is controlled within a specified range. By setting the liquid absorption amount x within the above range, the amount of the dispersion medium contained in the slurry of the present invention can be suppressed.

[0115] Regarding the formula (2), the slurry of the present invention preferably satisfies the following formula (2a), more preferably satisfies the following formula (2b), further preferably satisfies the following formula (2c), and particularly preferably satisfies the following formula (2d).

[0116] Formula (2a): 0 ≤ x ≤ 21

[0117] Formula (2b): 7 ≤ x ≤ 18

[0118] Formula (2c): 8 ≤ x ≤ 18

[0119] Formula (2d): 10 ≤ x ≤ 16

[0120] According to JIS 6217-4:2017, the liquid absorption amount (Sa, Sc) of the dispersion medium in every 100 g of the above electrode active material and conductive assistant can be obtained as follows.

[0121] - Liquid Absorption Amount Measurement Method -

[0122] In the measurement of the liquid absorption amount, an oil absorption measurement device (S-500 (trade name), manufactured by Asahi Soken Co., Ltd.) is used. For 15 g of the powder of the electrode active material or the conductive assistant, 0.5 g of the dispersion medium constituting the slurry is added each time and the torque is measured, so as to measure the added amount (mL) of the dispersion medium when the torque becomes the maximum (extreme). Based on the obtained value, the liquid absorption amount in every 100 g of the powder is calculated.

[0123] In the case where the above liquid absorption amount is measured when the slurry of the present invention contains a mixed solvent as the dispersion medium, this mixed solvent is used as the "dispersion medium constituting the above slurry" to measure the liquid absorption amount. In the case where the slurry of the present invention is a slurry for forming an electrode for a quasi-solid-state secondary battery, the dispersion medium (solvent obtained by removing the solute) constituting the non-aqueous electrolyte used in the preparation of the slurry is used for the above measurement.

[0124] In the formula (5), the liquid absorption amount Sa of the dispersion medium in every 100 g of the electrode active material is preferably 10 - 21 mL, more preferably 10 - 18 mL, more preferably 10 - 15 mL, and further preferably 11 - 15 mL.

[0125] The liquid absorption amount Sc of the dispersion medium in every 100 g of the conductive additive is preferably 200 to 1700 mL, more preferably 200 to 1500 mL, still more preferably 350 to 1500 mL, and further preferably 450 to 1400 mL. The liquid absorption amount Sc can be 700 to 1500 mL, can also be 800 to 1500 mL, or can also be 900 to 1500 mL.

[0126] The proportion da of the electrode active material in the total amount of the electrode active material and the conductive additive in the electrode forming paste is preferably 90.00 to 99.99% by mass, more preferably 95.00 to 99.99% by mass, still more preferably 97.00 to 99.95% by mass, and further preferably 98.00 to 99.90% by mass.

[0127] The proportion dc of the conductive additive in the total amount of the electrode active material and the conductive additive in the electrode forming paste is preferably 0.01 to 10.00% by mass, more preferably 0.01 to 5.00% by mass, and further preferably 0.10 to 2.00% by mass. The proportion dc of the conductive additive can also be set to 0.10 to 1.00% by mass.

[0128] The liquid absorption amounts of the electrode active material and the conductive additive can be appropriately controlled by these compositions, average particle diameters, BET specific surface areas, bulk densities, surface treatments, etc.

[0129] In the paste of the present invention, for the conductive additive, the formula (3) S BET ≥170 is satisfied. That is, the paste of the present invention uses a conductive additive with a relatively large BET specific surface area (m 2 / g).

[0130] The S of the conductive additive BET preferably satisfies the following formula (3a), more preferably satisfies the following formula (3b), still more preferably satisfies the following formula (3c), and further preferably satisfies the following formula (3d).

[0131] Formula (3a) S BET ≥300

[0132] Formula (3b) S BET ≥500

[0133] Formula (3c) S BET ≥700

[0134] Formula (3d) S BET ≥800

[0135] S BET The upper limit of is not particularly limited, but is actually 1500 m 2 / g. Thus, the S of the conductive additive BETPreferably, the following formula (3e) is satisfied, more preferably the following formula (3f) is satisfied, still more preferably the following formula (3g) is satisfied, and still more preferably the following formula (3h) is satisfied.

[0136] Formula (3e): 1500 ≥ S BET ≥ 300

[0137] Formula (3f): 1500 ≥ S BET ≥ 500

[0138] Formula (3g): 1500 ≥ S BET ≥ 700

[0139] Formula (3h): 1500 ≥ S BET ≥ 800

[0140] When the conductive additive has the above-mentioned large BET specific surface area, the surface of the conductive additive becomes uneven. Even if the addition amount of the conductive additive is reduced, a conductive network based on a good conductive additive can be formed, and the output characteristics can be improved when used as a battery. Thus, the addition amount of the conductive additive can be reduced. On the other hand, a conductive additive with a large BET specific surface area tends to cause aggregation of solid particles. In the present invention, this problem is solved by controlling the slurry in a manner that satisfies the above formula (4).

[0141] As described below, the S of the conductive additive can be measured by the BET method. BET .

[0142] - BET Specific Surface Area Measurement Method -

[0143] After drying 0.2 g of the conductive additive at 120 °C for 6 hours, measurement is carried out using BELSORP mini (trade name) manufactured by MICRO TRACK CO., LTD. under the following measurement conditions.

[0144] · Adsorption temperature: 77 K

[0145] · Adsorbed gas: N2

[0146] · Equilibrium time: 100 seconds

[0147] · Purge gas: He

[0148] The slurry of the present invention satisfies the formula (4) ΔE ≤ 30 (mN / m). The surface free energy (E d ) of the dispersion medium and the surface free energy (E cThe absolute value (ΔE) of the difference is within the above range, whereby the wettability (affinity) between the dispersion medium and the conductive additive becomes high. As a result, it is considered that the dispersion medium easily penetrates into the particle aggregates formed by the action of the conductive additive, and the interaction between the particles is reduced, thereby enabling the viscosity of the slurry to be reduced.

[0149] Equation (4) preferably satisfies the following equation (4a).

[0150] Equation (4a) ΔE ≤ 25

[0151] The lower limit of ΔE is not particularly limited, and preferably 2 ≤ ΔE.

[0152] ΔE is preferably 10 ≤ ΔE ≤ 30, more preferably 15 ≤ ΔE ≤ 30, and further preferably 20 ≤ ΔE ≤ 30. Also, ΔE is preferably 10 ≤ ΔE ≤ 25, preferably 15 ≤ ΔE ≤ 25, and preferably 20 ≤ ΔE ≤ 25.

[0153] The surface free energy (E d ) of the dispersion medium is preferably 10 to 80 mN / m, more preferably 10 to 60 mN / m, and further preferably 20 to 40 mN / m.

[0154] The surface free energy of the dispersion medium can be controlled by selecting the type of the dispersion medium, its combination, adding a dispersant for the electrode active material and the conductive additive to be described later, and the like.

[0155] The surface free energy (E c ) of the conductive additive is preferably 3 to 50 mN / m, more preferably 3.5 to 30 mN / m, more preferably 4.0 to 20 mN / m, more preferably 7.0 to 20 mN / m, and further preferably 16 to 20 mN / m.

[0156] The surface free energy of the conductive additive can be controlled by surface treatment or the like.

[0157] The surface free energy of the above-mentioned dispersion medium and the surface free energy of each conductive additive can be calculated as follows.

[0158] <Surface free energy measurement method>

[0159] 1) Surface free energy of the conductive additive

[0160] The surface free energy of the conductive additive can be obtained by the penetration rate method. The detailed content is described below.

[0161] Using a surface tension measuring instrument (device name: DY-700 (trade name), manufactured by Kyowa InterfaceScience Co., Ltd.), and measuring with a powder contact angle measuring instrument. Load 2.0 g of the powder of the conductive additive into a cylinder with an inner diameter of 1 cm (cross-sectional area S: 0.785 cm 2 ), and compress and fill the powder with a cylindrical rod having the same diameter as the inner diameter of the cylinder. Set the above cylinder on the powder contact angle measuring instrument, and allow 3 kinds of solvents (hexadecane, ethylene glycol, bromonaphthalene) to penetrate into the powder in the cylinder for 5 minutes (time t = 300 seconds) respectively, measure the penetration weight W L (g) of each solvent, and calculate W L 2 / t.

[0162] Substitute the W L 2 / t of each solvent thus obtained together with the following liquid density ρ L , liquid surface tension γ L and liquid viscosity η L into the following Washburn's formula, and calculate the contact angle cosθ of each solvent as follows.

[0163] The liquid density ρ L , liquid surface tension γ L and liquid viscosity η L of the above 3 kinds of solvents are reference values, and the following constants are adopted.

[0164] Hexadecane: ρ L = 0.775 g / mL, γ L = 27.6 mN / m, η L = 3.5 mPa·s

[0165] Ethylene glycol: ρ L = 1.11 g / mL, γ L = 47.7 mN / m, η L = 2 mPa·s

[0166] Bromonaphthalene: ρ L = 1.48 g / mL, γ L = 44.6 mN / m, η L = 2.3 mPa·s

[0167] [Formula 1]

[0168] Washburn's formula

[0169]

[0170] W: Penetration weight

[0171] t: Time

[0172] S: Cross-sectional area of the battery (powder layer filling part)

[0173] ε: Porosity

[0174] ρ: Liquid density

[0175] r: Capillary radius formed by particles in the powder layer

[0176] Y L : Liquid surface tension

[0177] n L : Liquid viscosity

[0178] θ: Contact angle formed by the liquid and the solid surface

[0179] Among the above three solvents, assuming that the contact angle of the solvent with the best wetting is 0°, the ε is determined by substituting W L calculated from the measured penetration weight W and penetration time t L 2 / t into Washburn's equation 2 r. Among them, ε 2 r is a constant determined by the powder type. (In Washburn's equation above, the unit of r is "m", and the porosity ε is a value in the range of 0.0 to 1.0.)

[0180] For each solvent, the W L 2 / t calculated from the measured weight and penetration time of the other two solvents and the ε 2 r obtained above are substituted into Washburn's equation to derive cosθ for each solvent

[0181] Substitute the cosθ of the two solvents obtained as above, the dispersion component and polar component of the surface free energy determined from the literature values into Fowkes' equation related to the components of the contact angle shown below, and solve the binary simultaneous equations for the dispersion component Y = γ SV d 、polar component X = γ SV h to obtain the dispersion component and polar component of the surface free energy of the powder

[0182] In addition, as the surface free energy of each of the above solvents, the respective constants described in Journal of the Adhesion Society of Japan, 8, 131 (1972) are used. The dispersion component of the surface free energy of each solvent (γ LVd ), the polar component (γ LV h ), and the sum of the dispersive component and the polar component (γ L ) are as follows.

[0183] Hexadecane: γ LV d = 27.6 mN / m, γ LV h = 0.0 mN / m, γ L = 27.6 mN / m

[0184] Ethylene glycol: γ LV d = 29.4 mN / m, γ LV h = 18.3 mN / m, γ L = 47.7 mN / m

[0185] Bromonaphthalene: γ LV d = 44.4 mN / m, γ LV h = 0.2 mN / m, γ L = 44.6 mN / m

[0186] The above operation (measurement of the penetration weight) was performed 4 times (N = 4), thereby obtaining the average values of the dispersive component and the polar component, respectively. The total amount of the average value Y of the dispersive component and the average value X of the polar component thus obtained was taken as the surface free energy (mN / m) of the powder. In the calculation of the surface free energy of the powder, the analysis software DYNALYZER was used.

[0187] [Equation 2]

[0188] Fowkes' equation

[0189]

[0190] γ SV d : Dispersive component of the surface free energy of the powder (between the powder and the gas) (mN / m)

[0191] γ LV d : Dispersive component of the surface free energy of the liquid (solvent) (between the liquid and the gas) (mN / m)

[0192] γ SV h : Polar component of the surface free energy of the powder (between the powder and the gas) (mN / m)

[0193] γ LVh : Polar component of the surface free energy of the liquid (solvent) (between the liquid and the gas) (mN / m)

[0194] γ L : γ LV d +γ LV h : Sum of the dispersive component and the polar component of the surface free energy of the liquid (mN / m)

[0195] 2) Surface free energy of the dispersion medium

[0196] Using a surface tension measuring instrument (device name: DY - 700 (trade name), manufactured by Kyowa Interface Science Co., Ltd.), and obtained by the Wilhelmy method. Specifically, make a platinum plate (perimeter L: 0.03 m) contact with the dispersion medium, measure the tension F (mN) applied to the plate and the contact angle θ between the platinum plate and the dispersion medium, and obtain the surface free energy γ (mN / m) by the following formula.

[0197] γ = F / Lcosθ

[0198] Perform the above operation 4 times, and take the average value of the obtained measurement values as the surface free energy of the dispersion medium (mN / m). The analysis software DYNALYZER was used for the calculation.

[0199] When the slurry contains a dispersant, use a dispersant dissolved at the same concentration as the slurry to measure the surface free energy of the dispersion medium.

[0200] As described above, the slurry of the present invention uses a conductive additive with a relatively large specific surface area, limits the amount of the dispersion medium to a relatively small amount in consideration of the liquid absorption amounts of the electrode active material and the conductive additive, and controls the relationship between the surface free energies of the conductive additive and the dispersion medium. As a result, the liquid amount in the slurry can be reduced. Although it is a high - concentration slurry obtained by using a conductive additive with a specified high specific surface area, the dispersion stability is more excellent, a smoother electrode can be formed, and from the perspective of forming the electrode active material layer, it helps to improve the manufacturing efficiency and quality of the battery.

[0201] In the slurry of the present invention, the content of the electrode active material in the slurry is preferably 45% by mass or more, more preferably 60% by mass or more, more preferably 65% by mass or more, more preferably 70% by mass or more, and further preferably 78% by mass or more.

[0202] In the slurry of the present invention, the content of the solid components (components other than the dispersion medium (solvent)) in the slurry is preferably more than 60% by mass, more preferably 65% by mass or more, and still more preferably 70% by mass or more. The content of the solid components is preferably 60 to 95% by mass, more preferably 65 to 92% by mass, still more preferably 70 to 90% by mass, still more preferably 72 to 88% by mass, and particularly preferably 75 to 85% by mass.

[0203] Each component constituting the slurry of the present invention will be described in more detail.

[0204] <Electrode active material>

[0205] (Positive electrode active material)

[0206] The positive electrode active material is preferably a material capable of reversibly inserting and releasing lithium ions. As long as the material has the above characteristics, there is no particular limitation, and it can be a transition metal oxide, an organic substance, sulfur, or other elements capable of forming a compound with Li, or a complex of sulfur and a metal.

[0207] Among them, as the positive electrode active material, a lithium-containing transition metal oxide is preferably used, and more preferably a lithium-containing transition metal oxide having a transition metal element M a (one or more elements selected from Co, Ni, Fe, Mn, Cu, and V). Further, elements M b (elements such as elements of Group 1 (Ia) and Group 2 (IIa) of the periodic table other than lithium, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, or B) may be mixed in the lithium-containing transition metal oxide. As the mixing amount, relative to the amount of the transition metal element M a (100 mol%), it is preferably 0 to 30 mol%. More preferably, a substance synthesized by mixing so that the molar ratio of Li / Ma becomes 0.3 to 2.2.

[0208] Specific examples of the lithium-containing transition metal oxide include (MA) a transition metal oxide having a layered rock salt structure, (MB) a transition metal oxide having a spinel structure, (MC) a lithium-containing transition metal phosphate compound, (MD) a lithium-containing transition metal halophosphate compound, and (ME) a lithium-containing transition metal silicate compound.

[0209] Specific examples of the transition metal oxide having a layered rock salt structure of (MA) include LiCoO2 (lithium cobaltate [LCO]), LiNi2O2 (lithium nickelate), LiNi 0.85 Co 0.10 Al 0.05 O2 (lithium nickel cobalt aluminate [NCA]), LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).

[0210] As specific examples of the transition metal oxides having a spinel structure as (MB), LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8 can be cited.

[0211] As the lithium-containing transition metal phosphate compounds as (MC), for example, olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, iron pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate) can be cited.

[0212] As the lithium-containing transition metal halogenated phosphate compounds as (MD), for example, iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F can be cited.

[0213] As the lithium-containing transition metal silicate compounds as (ME), for example, Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4 can be cited.

[0214] In the present invention, as the positive electrode active material, a lithium-containing transition metal phosphate compound as (MC) is preferred, and LiFePO4 is more preferred.

[0215] The shape of the positive electrode active material is not particularly limited, and a particulate shape is preferred.

[0216] The average particle diameter (average particle diameter converted to a sphere) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm, preferably 0.2 to 30 μm, more preferably 0.5 to 20 μm, and further preferably 0.8 to 10 μm.

[0217] In order to make the positive electrode active material into a specified particle diameter, a usual pulverizer or classifier can be used. The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.

[0218] In the case of using a commercially available positive electrode active material, the average particle diameter of the positive electrode active material is the value described in the manufacturer's catalog.

[0219] In the case where information on the average particle diameter of the manufacturer is not available or in the case of using a synthesized positive electrode active material, the value of the average particle diameter (median particle diameter D50 based on volume in water) obtained by dispersing the positive electrode active material in water and measuring it using a laser diffraction / scattering type particle size distribution measuring device (for example, Particle LA-960V2 manufactured by HORIBA, Ltd.) is adopted. This also applies to the average particle diameter of solid particles other than the positive electrode active material.

[0220] The chemical formula of the compound obtained by the above calcination method can be calculated by using inductively coupled plasma (ICP) emission spectrometry as a measurement method. As a simplified method, it can be calculated based on the mass difference of the powder before and after calcination.

[0221] The surface of the positive electrode active material can be surface-coated with other metal oxides such as oxides, carbon-based materials, etc.

[0222] As the surface coating material, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si, or Li can be mentioned. Specifically, spinel titanate, tantalum-based oxides, niobium-based oxides, and lithium niobate-based compounds can be mentioned. For example, Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, and Li3AlF6 can be mentioned. In addition, carbon-based materials such as C, SiC, and SiOC (carbon-doped silicon oxide) can also be used as the surface coating material.

[0223] From the viewpoint of increasing the electron conductivity to the desired level, the positive electrode active material can be surface-coated with a carbon-based material. The positive electrode active material is preferably surface-coated with carbon (C). In the presence of an additive (organic substance) as a carbon source, a carbon-based surface coating can be formed by calcining the positive electrode active material. As the additive, for example, styrene-maleic anhydride copolymer, polystyrene, polycarbonate, etc. can be used.

[0224] Furthermore, the surface of the positive electrode active material can be surface-treated with sulfur or phosphorus.

[0225] In addition, regarding the particle surface of the positive electrode active material, surface treatment can be performed with activated light or active gas (plasma, etc.) before and after the above surface coating.

[0226] The above positive electrode active materials can be used alone or in combination of two or more.

[0227] When forming the positive electrode active material layer, the mass (mg) (weight per unit area) of the positive electrode active material per unit area (cm 2 ) is not particularly limited and can be appropriately determined according to the designed battery capacity.

[0228] (Negative electrode active material)

[0229] The negative electrode active material is preferably a material capable of reversibly adsorbing (occluding) and releasing lithium ions. As long as the material has the above characteristics, there is no particular limitation, and examples include carbonaceous materials, silicon-based materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, or negative electrode active materials capable of forming alloys with lithium. Among them, from the viewpoint of reliability, carbonaceous materials or silicon-based materials can be preferably used.

[0230] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbonaceous materials obtained by calcining various synthetic resins such as carbon black (e.g., petroleum pitch), graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and PAN (polyacrylonitrile)-based resins or furfuryl alcohol resins can be cited. In addition, various carbon fiber types such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, mesophase microspheres, graphite whiskers, and plate-like graphite can also be cited.

[0231] As the metal oxides and metal composite oxides used as the negative electrode active material, as long as they are oxides capable of adsorbing and releasing lithium, there is no particular limitation. Amorphous oxides are preferred, and chalcogenides, which are reaction products between metal elements and Group 16 elements of the periodic table, can also be preferably cited. The amorphousness mentioned here means a material having a broad scattering band with a peak in the region of 20° to 40° in terms of 2θ value in X-ray diffraction using CuKα radiation, and may also have crystalline diffraction lines.

[0232] Among the compound groups composed of the above amorphous oxides and chalcogenides, amorphous oxides of semimetal elements and the above chalcogenides are more preferred, and oxides or chalcogenides composed of one kind of element selected from Group 13 (IIIB) to Group 15 (VB) of the periodic table, Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi, or a combination of two or more of these are particularly preferred. As specific examples of the preferred amorphous oxides and chalcogenides, for example, Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3, and Sb2S5 can be preferably cited.

[0233] From the viewpoint of the charge-discharge characteristics at a high current density, it is preferred that the metal (composite) oxide and the above chalcogenide contain at least one of titanium and lithium as a constituent. As the metal composite oxide containing lithium (lithium composite metal oxide), for example, a composite oxide of lithium oxide and the above metal (composite) oxide or the above chalcogenide can be cited. More specifically, Li2SnO2 can be cited.

[0234] The negative electrode active material also preferably contains titanium atoms. More specifically, since TiNb2O7 (titanium niobium oxide [NTO]), Li4Ti5O 12 (lithium titanate [LTO]) has a small volume change during the adsorption and release of lithium ions, it is preferred from the viewpoints of excellent rapid charge-discharge characteristics, suppression of electrode deterioration, and improvement of the life of the lithium ion secondary battery.

[0235] Regarding the lithium alloy as the negative electrode active material, as long as it is an alloy commonly used as the negative electrode active material of a secondary battery, it is not particularly limited. For example, a lithium aluminum alloy can be cited.

[0236] The negative electrode active material capable of forming an alloy with lithium is not particularly limited as long as it is a negative electrode active material commonly used as the negative electrode active material of a secondary battery. As such an active material, a negative electrode active material having a silicon atom or a tin atom, various metals such as Al and In can be cited. A negative electrode active material having a silicon atom (active material containing a silicon atom) capable of achieving a higher battery capacity is preferred, and an active material containing a silicon atom with a silicon atom content of 40 mol% or more of all constituent atoms is more preferred.

[0237] Generally speaking, compared with carbon anodes (such as graphite and acetylene black), anodes containing these anode active materials (for example, Si anodes containing active materials with silicon atoms, Sn anodes containing active materials with tin atoms) can adsorb more Li ions. That is, the adsorption amount of Li ions per unit mass increases. Therefore, the battery capacity (energy density) can be increased. As a result, it has the advantage of being able to extend the battery driving time.

[0238] As active materials containing silicon atoms, for example, silicon materials such as Si and SiOx (0 < x ≤ 1) can be cited. Further, alloys containing titanium, vanadium, chromium, manganese, nickel, copper or lanthanum (for example, LaSi2, VSi2) or organized active materials (for example, LaSi2 / Si) can be cited. In addition, active materials containing silicon atoms and tin atoms such as SnSiO3 and SnSiS3 can be cited. In addition, SiOx itself can be used as an anode active material (semi-metal oxide), and Si is generated through the operation of the battery, so it can be used as an active material (its precursor material) that can alloy with lithium.

[0239] As anode active materials with tin atoms, for example, Sn, SnO, SnO2, SnS, SnS2 can be cited. Further, the above-mentioned active materials containing silicon atoms and tin atoms can be cited. And it also contains a composite oxide with lithium oxide, for example, Li2SnO2.

[0240] In the present invention, the anode active material is preferably a carbonaceous material, and more preferably artificial graphite.

[0241] The shape of the anode active material is not particularly limited, but particle shape is preferred.

[0242] The average particle size (average particle size converted to a sphere) of the anode active material is preferably 0.1 - 60 μm, for example, preferably 0.5 - 50 μm, more preferably 1.0 - 40 μm, and further preferably 5.0 - 30 μm.

[0243] In order to make a specified particle size, ordinary crushers or classifiers can be used. For example, a mortar, ball mill, sand mill, vibration ball mill, satellite ball mill, planetary ball mill, rotary air flow type jet mill or sieve, etc. can be preferably used. During pulverization, wet pulverization can also be carried out in the presence of an organic solvent such as water or methanol. In order to make the desired particle size, classification is preferably carried out. As the classification method, there is no particular limitation, and according to needs, a sieve, air classifier, etc. can also be used. Classification can use dry and wet methods simultaneously.

[0244] The above-mentioned anode active materials can be used alone or in combination of two or more.

[0245] When forming the negative electrode active material layer, the mass (mg) (weight per unit area) of the negative electrode active material per unit area (cm 2 ) of the negative electrode active material layer is not particularly limited and can be appropriately determined according to the designed battery capacity.

[0246] The chemical formula of the compound obtained by the above calcination method can be calculated by using inductively coupled plasma (ICP) emission spectrometry as the measurement method. As a simplified method, it can be calculated based on the mass difference of the powder before and after calcination.

[0247] <Conductive Additive>

[0248] As the conductive additive, as long as the above formula (3) is satisfied, there is no particular limitation, and a conductive additive known as a general conductive additive can be used. For example, it can be graphite-based such as natural graphite and artificial graphite as electron conductive materials, carbon blacks such as acetylene black, Ketjen black, and furnace black, amorphous carbon such as needle coke, carbon fiber-based such as vapor-grown carbon fiber or carbon nanotube, carbonaceous materials such as graphene or fullerene, metal powders and metal fibers such as copper and nickel, and conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives.

[0249] In the present invention, the conductive additive is preferably a carbonaceous material, more preferably acetylene black and Ketjen black.

[0250] When the positive electrode active material and the conductive additive are used simultaneously, a conductive additive that does not intercalate and release Li and does not function as an active material during charge and discharge of the battery is used as the conductive additive. Thus, among the conductive additives, a conductive additive that functions as an active material in the active material layer during charge and discharge of the battery is classified as an active material, rather than a conductive additive. Whether it functions as an active material during charge and discharge of the battery is not determined by a single factor and can be determined according to the combination with the active material.

[0251] Examples of commercially available products of the conductive additive are as follows.

[0252] Ketjen black: Carbon ECP (BET specific surface area = 890 m 2 / g), Carbon ECP600JD (BET specific surface area = 1480 m 2 / g), Carbon ECP200L (BET specific surface area = 430 m 2 / g) (all manufactured by Lion Corporation),

[0253] Carbon black: LITX300 (BET specific surface area = 180 m 2 / g), PBX09 (BET specific surface area = 230 m 2 / g), PBX51 (BET specific surface area = 1350 m 2 / g), LITXmax90 (BET specific surface area = 1400 m 2 / g) (all manufactured by CABOT Corporation)

[0254] CNT: BT1001M (BET specific surface area = 272 m 2 / g), BT1003M (BET specific surface area = 230 m 2 / g) (both from LG Corporation)

[0255] One type of conductive aid can be used, or two or more types can be used.

[0256] The shape of the conductive aid is not particularly limited, but particulate form is preferred.

[0257] The average particle size (average particle size in terms of spherical equivalent) of the conductive aid is not particularly limited. For example, it is preferably 0.01 - 50 μm, more preferably 0.1 - 10 μm, and still more preferably 0.2 - 2.0 μm.

[0258] The bulk density (g / L) of the conductive aid is not particularly limited. For example, the bulk density is preferably 40 g / L or less, more preferably 35 g / L or less. The lower limit is not particularly limited, but is actually 10 g / L or more. Thus, the bulk density of the conductive aid is preferably 10 - 40 g / L, more preferably 10 - 35 g / L. The bulk density can also be set to 20 - 35 g / L.

[0259] The bulk density of the conductive aid can be measured as follows.

[0260] - Bulk Density Measurement Method -

[0261] Gently place 5 g of the sample into a 250 mL graduated cylinder. Level the upper surface of the powder layer without compaction and read the bulk volume (mL) at the smallest scale unit. Calculate the bulk density (g / mL) by dividing the sample weight (g) by the bulk volume. Repeat the test 3 times and take the average value as the bulk density of the conductive aid.

[0262] The conductive aid can be surface - treated. The surface free energy can be controlled by surface - treating.

[0263] As the surface - treatment method, it is not particularly limited, but surface - treatment using a chemical treatment agent and atomic layer deposition (ALD) treatment are preferred.

[0264] As chemical treatment agents, organosilicon compounds (more preferably silane coupling agents), organic phosphonic acid compounds, etc. are preferred. Examples include methyltrimethoxysilane (MTMS), octadecyltrimethoxysilane, hexamethyldisilazane, tetraethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, 3-aminopropyltriethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, trimethoxy(octyl)silane, 1H,1H,2H,2H-perfluorooctylphosphonic acid, 1-octylphosphonic acid, perfluoropolyethertriethoxysilane (KY1903 (trade name)), etc.

[0265] In ALD treatment, as the deposited layer, examples include HfO2, SiO2, ZrO2, Ta2O5, TiO2, etc.

[0266] <Dispersion medium>

[0267] The dispersion medium can be water or a non-aqueous solvent in the first mode (slurry for forming electrodes of general non-aqueous electrolyte secondary batteries). In the second mode (slurry for forming electrodes of quasi-solid-state secondary batteries), water is not used, but a non-aqueous solvent is used.

[0268] As the non-aqueous solvent, aprotic organic solvents are preferred, and among them, aprotic organic solvents having 2 to 10 carbon atoms are more preferred.

[0269] Examples of such non-aqueous solvents include chain or cyclic carbonate compounds, lactone compounds, chain or cyclic ether compounds, ester compounds, nitrile compounds, amide compounds, oxazolidinone compounds, nitro compounds, chain or cyclic sulfone or sulfoxide compounds, and phosphate ester compounds.

[0270] In addition, compounds having an ether bond, a carbonyl bond, an ester bond, or a carbonate bond are preferred. These compounds can have substituents.

[0271] As non-aqueous solvents, for example, ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, γ-butyrolactone, γ-valerolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl pivalate, ethyl pivalate, acetonitrile, glutaronitrile, adiponitrile, methoxyacetonitrile, 3-methoxypropionitrile, N,N-dimethylformamide, N-methylpyrrolidone (NMP), N-methyloxazolidinone, N,N'-dimethylimidazolidinone, nitromethane, nitroethane, sulfolane, trimethyl phosphate, dimethyl sulfoxide or dimethyl sulfoxide phosphate, etc. can be cited. They can be used alone or two or more of them can be used simultaneously. Among them, at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and γ-butyrolactone is preferred, and a combination of a high-viscosity (high dielectric constant) solvent such as ethylene carbonate or propylene carbonate (for example, relative dielectric constant ε≥30) and a low-viscosity solvent such as dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate (for example, viscosity ≤1 mPa·s) is more preferred. By using a mixed solvent of such a combination, the dissociation property of the electrolyte salt and the mobility of ions are improved. The above non-aqueous solvents are particularly preferably a combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.

[0272] In addition, the non-aqueous solvents used in the present invention are not limited to these.

[0273] When the slurry in the present invention is a slurry for forming a positive electrode in the first mode, the dispersion medium is preferably N-methylpyrrolidone (NMP) or a mixed solvent of N-methylpyrrolidone (NMP) and dimethyl carbonate (DMC).

[0274] When the slurry in the present invention is a slurry for forming a negative electrode in the first mode, the dispersion medium is preferably water or N-methylpyrrolidone (NMP).

[0275] When the slurry in the present invention is a slurry for forming an electrode in the second mode, the dispersion medium is preferably a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC).

[0276] <Electrolyte solution>

[0277] When the slurry in the present invention is a slurry for forming an electrode in the second mode, an electrolyte is added to the dispersion medium to be used as an electrolyte solution.

[0278] As the dispersion medium, the above non-aqueous solvent is used.

[0279] As the electrolyte, an electrolyte used in the electrolyte of a quasi-solid secondary battery can be used. Preferred metal salts include lithium salts, potassium salts, sodium salts, calcium salts, magnesium salts, etc.

[0280] As the lithium salt, a lithium salt commonly used in the electrolyte of a lithium ion secondary battery is preferred. For example, the following lithium salts can be cited.

[0281] (L-1) Inorganic lithium salts: inorganic fluoride salts such as LiPF6, LiBF4, LiAsF6, LiSbF6, etc., perhalate salts such as LiClO4, LiBrO4, LiIO4, etc., inorganic chloride salts such as LiAlCl4, etc.

[0282] (L-2) Fluorine-containing organic lithium salts: perfluoroalkylsulfonates such as LiCF3SO3, perfluoroalkylsulfonimide salts such as LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(FSO2)2, LiN(CF3SO2)(C4F9SO2), etc., perfluoroalkylsulfonylmethylide salts such as LiC(CF3SO2)3, perfluoroalkylfluorophosphates such as Li[PF5(CF2CF2CF3)], Li[PF4(CF2CF2CF3)2], Li[PF3(CF2CF2CF3)3], Li[PF5(CF2CF2CF2CF3)], Li[PF4(CF2CF2CF2CF3)2], Li[PF3(CF2CF2CF2CF3)3], etc.

[0283] (L-3) Oxaloborates: lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, etc.

[0284] Among these, LiPF6, LiBF4, LiAsF6, LiSbF6, LiClO4, Li(R f1 SO3), LiN(R f1 SO2)2, LiN(FSO2)2 or LiN(R f1 SO2)(R f2 SO2) are preferred, LiPF6, LiBF4, LiN(R f1 SO2)2, LiN(FSO2)2 or LiN(R f1 SO2)(R f2 SO2) are more preferred, and LiPF6 is particularly preferred. Among them, R f1 and R f2 each represent a perfluoroalkyl group, and the number of carbon atoms is preferably 1 to 6.

[0285] In addition, the lithium salt used in the electrolyte of the present invention can be used alone or in any combination of two or more.

[0286] In the electrolyte, the concentration of the lithium salt is usually 10.0 to 50.0% by mass, preferably 15.0 to 30.0% by mass. As the molar concentration, it is preferably 0.5 to 1.5 M.

[0287] <Dispersant>

[0288] The slurry of the present invention may contain a dispersant. The dispersant has an adsorption site and a repulsion site that adsorb to the electrode active material and the conductive auxiliary agent, and has a function of suppressing the aggregation of the active materials and the conductive auxiliary agents with each other.

[0289] As the dispersant, a dispersant commonly used in non-aqueous electrolyte secondary batteries can be appropriately selected and used. For example, PVP (polyvinylpyrrolidone), PEG (polyethylene glycol), etc. can be used.

[0290] As the dispersant, the following commercially available products can also be used.

[0291] BYK-ET3004, BYK-ET3034, BYK-ET3003, DISPERBYK-102, DISPERBYK-106, DISPERLAST-1142 (all are trade names, manufactured by BYK-Chemie GmbH), Tween20, Triton-X-100 (all are trade names, manufactured by Tokyo Chemical Industry Co., Ltd.).

[0292] In the slurry of the present invention, relative to 100 parts by mass of the total amount of the electrode active material and the conductive auxiliary agent, the content of the dispersant is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 1 part by mass.

[0293] <Other Components>

[0294] The slurry of the present invention can also contain a binder, an ionic liquid, a thickener, an antifoaming agent, a leveling agent, a dehydrating agent, an antioxidant, etc. as needed. These substances that can be used are those commonly used in non-aqueous electrolyte secondary batteries.

[0295] As the binder, polyvinylidene fluoride (PVdF) and styrene-butadiene copolymer (SBR) are preferred.

[0296] Relative to 100 parts by mass of the electrode active material, the content of the binder is preferably 0.1 to 8 parts by mass, more preferably 0.5 to 2 parts by mass.

[0297] As the thickener, carboxymethyl cellulose (CMC) is preferred.

[0298] Relative to 100 parts by mass of the total amount of the electrode active material and the conductive auxiliary agent, the content of the thickener is preferably 0.1 to 2.0 parts by mass, more preferably 0.5 to 1.5 parts by mass.

[0299] [Non-aqueous electrolyte secondary battery]

[0300] The non-aqueous electrolyte secondary battery of the present invention (hereinafter, also referred to as "the secondary battery of the present invention") successively includes a positive electrode, a separator, and a negative electrode, and the slurry of the present invention is used in the formation of the positive electrode active material layer and / or the negative electrode active material layer.

[0301] Before describing the secondary battery of the present invention, the structure of a general non-aqueous electrolyte secondary battery will be described.

[0302] Figure 1 It is a cross-sectional view schematically showing the laminated structure of a general non-aqueous electrolyte secondary battery 10 including the working electrode during battery operation. The non-aqueous electrolyte secondary battery 10 has a laminated structure (hereinafter, also referred to as an electrode laminate) that successively includes a negative electrode current collector 1, a negative electrode active material layer 2, a separator 3, a positive electrode active material layer 4, and a positive electrode current collector 5 when viewed from the negative electrode side. The space between the negative electrode active material layer 2 and the positive electrode active material layer 4 is filled with a non-aqueous electrolyte (not shown) and separated by the separator 3. The separator 3 has pores and functions as a separator between the positive and negative electrodes that insulates the positive and negative electrodes while allowing the electrolyte and ions to pass through the pores in the state of using a normal battery. With this structure, for example, in the case of a lithium-ion secondary battery, during charging, electrons (e - ) are supplied to the negative electrode side through an external circuit, and at the same time, lithium ions (Li + ) move from the positive electrode to the negative electrode through the electrolyte and accumulate in the negative electrode. On the other hand, during discharging, the lithium ions (Li + ) accumulated in the negative electrode return to the positive electrode side through the electrolyte and supply electrons to the working part 6. In the illustrated example, a light bulb is adopted in the working part 6 and is lit by discharging.

[0303] Next, the basic structural features of the quasi-solid-state secondary battery will be described. As described above, in the quasi-solid-state secondary battery, the electrode active material layer is an electrode slurry layer in which the electrode active material is dispersed in a non-aqueous electrolyte. Thus, in terms of the view that the electrode active material layer is a slurry (suspension, dispersion) dispersed in a non-aqueous electrolyte, its structure is different from that of a general non-aqueous electrolyte secondary battery.

[0304] That is, in a general non-aqueous electrolyte secondary battery, a coating liquid is prepared by dispersing an electrode active material in a medium not containing an electrolyte, the coating liquid is coated on a current collector to form a coating film, and the coating film is dried to form a thin-film electrode active material layer. A binder is usually contained in the coating liquid to firmly bond the electrode active material particles together to form a hard electrode active material layer. Since the non-aqueous electrolyte exists in such a manner on the electrode active material layer thus formed (between the negative electrode active material layer and the positive electrode active material layer), even if there is a part in the electrode active material layer into which the non-aqueous electrolyte can penetrate, the whole is in the state of a hard solid particle layer rather than a slurry layer.

[0305] In contrast, in a quasi-solid state secondary battery, the electrode active material layer is an electrode slurry layer formed by dispersing solid particles containing an electrode active material and a conductive additive in a non-aqueous electrolyte obtained by dissolving a lithium salt (electrolyte) in a non-aqueous solvent. When the electrode slurry layer functions as an electrode active material layer, strong adhesiveness between the electrode active material particles is not required, and thus the electrode slurry layer usually does not contain a binder. The electrode active material layer is the electrode slurry layer and the electrode slurry layer contacts the separator. Other than this, the basic layer structure of the quasi-solid state secondary battery is the same as Figure 1 the layer structure shown.

[0306] In the case where the secondary battery of the present invention is a general non-aqueous electrolyte secondary battery, the positive electrode active material layer and / or the negative electrode active material layer is a layer obtained by coating the slurry of the first method of the present invention and drying it as needed.

[0307] In the case where the secondary battery of the present invention is a quasi-solid state secondary battery, the positive electrode active material layer and / or the negative electrode active material layer is a layer formed by the slurry of the second method of the present invention.

[0308] In the secondary battery of the present invention, it is preferable to use the slurry of the present invention to form both the positive electrode active material layer and the negative electrode active material layer.

[0309] As the electrode active material layer when forming any one of the positive electrode active material layer and the negative electrode active material layer using an electrode forming slurry other than the slurry of the present invention, a general electrode active material layer can be used.

[0310] In the secondary battery of the present invention, except for using the slurry of the present invention in the formation of the positive electrode active material layer and / or the negative electrode active material layer, the positive electrode active material, the positive electrode current collector, the negative electrode active material, the negative electrode current collector, the separator and other materials and components are not particularly limited. These materials and components can be appropriately applied to the materials and components used in ordinary secondary batteries. Regarding the components and manufacturing methods commonly used in these secondary batteries, for example, Japanese Unexamined Patent Application Publication No. 2016-201308, Japanese Unexamined Patent Application Publication No. 2005-108835, Japanese Unexamined Patent Application Publication No. 2012-185938, International Publication No. 2018 / 135395, etc. can be appropriately referred to.

[0311] In the secondary battery of the present invention, the thickness of the positive electrode active material layer is not particularly limited. For example, it can be set to 5 to 500 μm, preferably 20 to 200 μm.

[0312] In the secondary battery of the present invention, the thickness of the negative electrode active material layer is not particularly limited. For example, it can be set to 5 to 500 μm, preferably 20 to 200 μm.

[0313] [Manufacturing Method of Non-aqueous Electrolyte Secondary Battery]

[0314] The manufacturing method of the non-aqueous electrolyte secondary battery of the present invention includes the step of coating the slurry of the present invention on the electrode current collector to form an electrode active material layer.

[0315] The coating method of the slurry is not particularly limited. For example, a roll coater can be used for coating or drop coating, or after uniformly coating the slurry on the current collector, stamping (roll stamping or flat stamping) can be performed, or the slurry can be set and spread in a frame of a specified thickness for coating.

[0316] When the secondary battery obtained by the manufacturing method of the secondary battery of the present invention is an ordinary secondary battery, the manufacturing method of the present invention may include the step of drying the slurry of the present invention.

[0317] Regarding the manufacturing method of the non-aqueous electrolyte secondary battery of the present invention, except for using a specific slurry layer to form an electrode active material layer, ordinary methods can also be appropriately adopted. For example, Japanese Unexamined Patent Application Publication No. 2016-201308, Japanese Unexamined Patent Application Publication No. 2005-108835, Japanese Unexamined Patent Application Publication No. 2012-185938, Japanese Unexamined Patent Application Publication No. 2017-147222, etc. can be appropriately referred to.

[0318] For example, the non-aqueous electrolyte secondary battery of the present invention can be mounted on electronic devices such as laptop computers, pen input computers, mobile computers, e-book readers, mobile phones, cordless phone handsets, pagers, handheld terminals, portable fax machines, portable copiers, portable printers, stereo headphones, video cameras, liquid crystal TVs, handheld vacuum cleaners, portable CDs, floppy disks, electric shavers, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power supplies, etc. Moreover, as consumer goods, it can be mounted on automobiles, electric vehicles, motors, lighting fixtures, toys, game machines, load regulators, clocks, flashlights, cameras, and medical devices (such as pacemakers, hearing aids, and shoulder massagers), etc. In addition, it can be used as various military supplies and aerospace supplies. And it can also be combined with solar cells.

[0319] Hereinafter, the present invention will be further described in detail based on examples. In addition, the present invention should not be construed as being limited thereto.

[0320] Examples

[0321] [Preparation of Electrode-Forming Paste]

[0322] An electrode-forming paste was prepared using the following components.

[0323] <Electrode Active Material>

[0324] ·LFP1: LiFePO4, manufactured by GELON Co., Ltd. (average particle size (average particle size converted to a sphere) 0.9 μm)

[0325] ·LFP2: LiFePO4, manufactured by Gelon Co., Ltd. (average particle size (average particle size converted to a sphere) 1.2 μm)

[0326] ·LFP3: LiFePO4, manufactured by Gelon Co., Ltd. (average particle size (average particle size converted to a sphere) 1.7 μm)

[0327] ·LFP4: LiFePO4, manufactured by Gelon Co., Ltd. (average particle size (average particle size converted to a sphere) 2.5 μm)

[0328] ·Graphite1: Artificial graphite, UF-G5 (product name), manufactured by SHOWA DENKO K.K. (average particle size (average particle size converted to a sphere) 3 μm)

[0329] ·Graphite2: Artificial graphite, UF-G10 (product name), manufactured by SHOWA DENKO K.K. (average particle size (average particle size converted to a sphere) 5 μm)

[0330] ·Graphite 3: Artificial graphite, UF-G30 (product name), manufactured by SHOWA DENKO K.K. (average particle size (average particle size converted to spherical shape) 10 μm)

[0331] <Conductive aid>

[0332] ·AB1: Acetylene black, Li100 (product name), manufactured by Denka Company Limited

[0333] ·AB2: Acetylene black, Li435 (product name), manufactured by Denka Company Limited

[0334] ·CB1: Carbon black, LITX300 (product name), manufactured by CABOT Corporation

[0335] ·CB2: Carbon black, PBX09 (product name), manufactured by CABOT Corporation

[0336] ·KB1: Ketjen black, Carbon ECP (product name), manufactured by Lion Corporation

[0337] ·KB1H: Ketjen black with the following controlled bulk density

[0338] Using a planetary ball mill (Fritsch Co., Ltd., P-7 (product name)), 30 g of zirconia beads (diameter 3 mm) were added to a 45 mL zirconia container, 10 g of the powder of KB1 (bulk density 38 g / L) was added, and they were mixed at 300 rpm for 24 hours to break up the agglomeration. Thus, a conductive aid powder (KB1H) with a bulk density of 32 g / L was obtained.

[0339] ·KB1HS: Ketjen black obtained by further surface-treating the Ketjen black (KB1H) with the above-controlled bulk density as follows

[0340] 95 parts by mass of ethanol, 5 parts by mass of water, and 3 parts by mass of acetic acid were added, and further 10 parts by mass of KB1H was added and stirred for 10 minutes. Then, 2 parts by mass of methyltrimethoxysilane (MTMS) was added and stirred for 5 minutes. Then, it was allowed to stand and the liquid was removed by decantation. After washing twice with ethanol, it was heated under vacuum at 110 °C for 24 hours.

[0341] ·KB2: Ketjen black, ECP600JD (product name), manufactured by Lion Corporation

[0342] <Dispersion medium>

[0343] ·NMP: N-Methylpyrrolidone

[0344] · DMC: Dimethyl Carbonate

[0345] · EMC: Ethyl Methyl Carbonate

[0346] 1) Preparation of Non-aqueous Electrolyte

[0347] A non-aqueous electrolyte (Electrolyte 1) was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a mass ratio of EC:DMC:EMC = 3:4:3, and mixing LiPF6 as a lithium salt to a concentration of 1 M in the resulting mixed solvent.

[0348] 2) Preparation of Positive Electrode Slurry (First Method)

[0349] · Comparative Examples 1 - 5, Examples 1 - 11

[0350] An electrode active material, a conductive additive, a dispersion medium, and polyvinylidene fluoride (PVdF) as a binder described in Table 1 were mixed to obtain a positive electrode slurry (slurry for electrode formation). The content of each component in this positive electrode slurry was set as follows.

[0351] The electrode active material and the conductive additive were set to amounts such that the content of each of the electrode active material and the conductive additive in the total amount of the electrode active material and the conductive additive became the ratio (mass%) described in Table 1.

[0352] In the amount of the dispersion medium in the slurry, the amount per 100 g of the total amount of the electrode active material and the conductive additive in the slurry became the amount described in Table 1.

[0353] With respect to 100 parts by mass of the electrode active material, 6 parts by mass of the binder was used.

[0354] Thereby, the positive electrode slurries of Comparative Examples 1 - 5 and Examples 1 - 11 were obtained. The content of the electrode active material in the positive electrode slurry of Example 1 was 70.8 mass%.

[0355] In addition, in Comparative Example 4 and Examples 9 - 11, a dispersion medium in which the surface free energy was controlled by mixing a plurality of dispersion media was used. Specifically, a dispersion medium obtained by mixing N-methylpyrrolidone (NMP) and dimethyl carbonate (DMC) in a mass ratio of NMP:DMC = 3:2 was used. In Table 1, it is described as "NMP + DMC". This dispersion medium was also used in Comparative Example 8 described later.

[0356] In Comparative Example 5, a dispersion medium obtained by mixing N-methylpyrrolidone (NMP) and water (Water) at a mass ratio of NMP:Water = 2:3 was used. In Table 1, it is recorded as "NMP+Water". This dispersion medium was also used in Comparative Examples 6 and 10 described later.

[0357] · Example 12

[0358] As a dispersant, 1 part by mass of ET3004 (trade name) manufactured by BYK-Chemie GmbH (alkylammonium salt of a copolymer containing an acidic group) was added to 100 parts by mass in total of the electrode active material and the conductive assistant, and a dispersion medium obtained by mixing N-methylpyrrolidone (NMP) and dimethyl carbonate (DMC) at a mass ratio of NMP:DMC = 2:3 was used. Except for this, the positive electrode paste of Example 12 was obtained in the same manner as in Example 10. In Table 1, the above dispersion medium is recorded as "NMP+DMC2".

[0359] 3) Preparation of positive electrode paste (second method)

[0360] · Example 20

[0361] Using a centrifugal planetary mixer (manufactured by THINKY CORPORATION: Awatori Rentaro (trade name)), the electrode active material, conductive assistant, and non-aqueous electrolyte recorded in Table 1 were mixed at 1250 rpm for 90 seconds to obtain a positive electrode paste. The content of each component in this positive electrode paste was set as follows.

[0362] The electrode active material and the conductive assistant were set to amounts such that the respective contents of the electrode active material and the conductive assistant in the total amount of the electrode active material and the conductive assistant became the ratios (mass%) recorded in Table 1.

[0363] In the amount of the non-aqueous electrolyte in the paste, the amount per 100 g of the total amount of the electrode active material and the conductive assistant in the paste was set to the amount recorded in Table 1.

[0364] Thus, the positive electrode paste of Example 20 was obtained. In addition, for convenience, the case where the above electrolyte 1 was used as the non-aqueous electrolyte is shown in the column of "dispersion medium type" in the table. The dispersion medium in electrolyte 1 is a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC).

[0365] 4) Preparation of negative electrode paste (first method)

[0366] · Comparative Examples 6 to 10, Example 13

[0367] The electrode active material, conductive assistant, dispersion medium, styrene-butadiene copolymer (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener described in Table 1 were mixed to obtain a negative electrode paste (paste for electrode formation). The contents of the respective components in the negative electrode paste were set as follows.

[0368] The electrode active material and the conductive assistant were set to amounts such that the respective contents of the electrode active material and the conductive assistant in the total amount of the electrode active material and the conductive assistant became the ratios (mass %) described in Table 1.

[0369] In the amount of the dispersion medium in the paste, the amount per 100 g of the total amount of the electrode active material and the conductive assistant in the paste became the amount described in Table 1.

[0370] With respect to 100 parts by mass of the electrode active material, 1 part by mass of the binder was used, and with respect to 100 parts by mass of the electrode active material, 1 part by mass of the thickener was used.

[0371] Thus, the negative electrode pastes of Comparative Examples 6 to 10 and Example 13 were obtained.

[0372] 5) Preparation of Negative Electrode Paste (Second Method)

[0373] · Example 21

[0374] The electrode active material, conductive assistant, and non-aqueous electrolyte described in Table 1 were mixed for 90 seconds at 1250 rpm using a centrifugal planetary mixer (manufactured by THINKY CORPORATION: Awatori Rentaro (trade name)) to obtain a negative electrode paste. The contents of the respective components in the negative electrode paste were set as follows.

[0375] The electrode active material and the conductive assistant were set to amounts such that the contents of the electrode active material and the conductive assistant in the total amount of the electrode active material and the conductive assistant became the ratios (mass %) described in Table 1.

[0376] In the amount of the non-aqueous electrolyte in the paste, the amount per 100 g of the total amount of the electrode active material and the conductive assistant in the paste became the amount described in Table 1.

[0377] Thus, the negative electrode paste of Example 21 was obtained.

[0378] In order to confirm the adequacy of the formulas (1) to (4) of each electrode paste obtained above, regarding the components used in the preparation process of each paste, the liquid absorption amount of the dispersion medium in every 100 g of the electrode active material, the liquid absorption amount of the dispersion medium in every 100 g of the conductive additive, the BET specific surface area of the conductive additive, and the surface free energy of the dispersion medium and the conductive additive were respectively obtained as described above. In addition, the bulk density of the conductive additive was confirmed as described above.

[0379] In Table 1, the types of the electrode active material, the conductive additive, and the dispersion medium constituting the electrode paste, the liquid absorption amounts of the dispersion medium in every 100 g of the electrode active material and the conductive additive ("active material liquid absorption amount" and "conductive additive liquid absorption amount" in Table 1), the proportions of the electrode active material and the conductive additive in the total amount of the electrode active material and the conductive additive ("active material proportion" and "conductive additive proportion" in Table 1), the amount of the dispersion medium in every 100 g of the total amount of the electrode active material and the conductive additive ("dispersion medium amount" in Table 1), and the solid component concentration and the active material concentration in the electrode paste are shown in a summary.

[0380] In Table 2, the adequacy of the formulas (1) to (4) is shown. In the column of "Surface E difference" in Table 2, the absolute value of the difference between the surface free energy of the dispersion medium and the surface free energy of the above-mentioned conductive additive is recorded. In the column of "Surface E of conductive additive", the surface free energy of the conductive additive is recorded. In "Surface E of dispersion medium", the surface free energy of the dispersion medium is recorded. In the column of "Dispersant" in Table 2, the presence or absence of the dispersant is also recorded together. "None" means that no dispersant is used. In the case where a dispersant is used, the type of the dispersant used is recorded. For convenience, regarding the case where the conductive additive is surface-treated without adding a dispersant, the type of the surface treatment agent used is recorded in the "Dispersant" column.

[0381]

[0382]

[0383] The viscosity and manufacturing adaptability of the obtained electrode paste were evaluated. The manufacturing adaptability was evaluated from the viewpoints of the dispersion stability after the production of the electrode paste, the drying time required for forming the electrode active material layer, and the coating adaptability. The specific evaluation methods are shown below.

[0384] [Paste Viscosity Measurement Method]

[0385] E-type viscometer (TV-35, manufactured by Toki Sangyo Co., Ltd.), standard conical rotor (1°34’×R24). The sample cup was adjusted to 25°C, and 1.1 mL of the electrode paste obtained above was put in. The sample cup was set on the main body and maintained for 5 minutes until the temperature became constant. Then, the viscosity measured at a rotational speed of 50 rpm was set as the viscosity value. The obtained viscosity value was evaluated according to the following evaluation criteria.

[0386] - Evaluation Criteria -

[0387] A: Less than 100 mPa·s

[0388] B: 100 mPa·s or more and less than 1000 mPa·s

[0389] C: 1000 mPa·s or more and less than 5000 mPa·s

[0390] D: 5000 mPa·s or more and less than 10000 mPa·s

[0391] E: 10000 mPa·s or more and less than 100000 mPa·s

[0392] F: 100000 mPa·s or more

[0393] [Dispersion Stability]

[0394] The dispersion stability was evaluated based on the precipitation state of the particles after the paste was prepared.

[0395] 90 mL of each of the electrode pastes obtained above was put into a vial (100 ml, diameter 30 mm) and allowed to stand for 72 hours to form a supernatant region above the precipitate in the vertical direction.

[0396] After 72 hours, the height (H S ) of the above-mentioned supernatant region was measured using a scale. Also, the height of the whole paste (the sum of the heights of the precipitate and the supernatant) (H T ) was measured. The ratio (H S ) of the obtained height of the supernatant region to the height of the whole paste (H T ) (H S / H T ×100) was set as the index of dispersion stability. The obtained value was evaluated according to the following evaluation criteria.

[0397] - Evaluation Criteria -

[0398] A: Less than 2%

[0399] B: 2% or more and less than 4%

[0400] C: More than 4% and less than 10%

[0401] D: More than 10% and less than 15%

[0402] E: More than 15% and less than 30%

[0403] F: 30% or more

[0404] [Drying time required to form the electrode active material layer]

[0405] Each of the electrode pastes obtained above was coated on an aluminum foil (length: 300 mm, width: 200 mm) so that the dried thickness became approximately 80 μm. In a thermostat, the obtained coated material was dried at 240°C to obtain an electrode layer. Starting from the beginning of drying, the weight of the coated material was measured every 0.5 minutes, and the time from the start of drying until the weight of the coated material became the same as the weight measured previously was defined as the drying time.

[0406] In addition, the positive electrode paste of Example 20 and the negative electrode paste of Example 21 are both electrode pastes for quasi-solid-state secondary batteries and do not require drying, so they were excluded from the evaluation targets.

[0407] The obtained drying time was applied to the following evaluation criteria for evaluation.

[0408] -Evaluation criteria-

[0409] A: Less than 1 minute

[0410] B: 1 minute or more and less than 10 minutes

[0411] C: 10 minutes or more and less than 20 minutes

[0412] D: 20 minutes or more and less than 30 minutes

[0413] E: 30 minutes or more and less than 60 minutes

[0414] F: 60 minutes or more

[0415] [Smoothness of the electrode surface]

[0416] The coating adaptability was evaluated using the smoothness of the electrode surface as an index.

[0417] Five places in the central part of the electrode layer with aluminum foil (after drying) obtained in the above drying time measurement were punched with a diameter of 10 mm, the film thickness (μm) at the center of each of the obtained punched pieces was measured, and the average value (T C)。 Also, at a position 5 in the region 1 cm from the end of the coating, stamping is performed with a diameter of 10 mm, the film thickness (μm) at the center of each obtained stamped piece is measured, and the average value (T S ) is calculated. Calculate the deviation of the average film thickness between the side portion and the central portion ((|T C -T S |) / T C ×100), and the obtained value is evaluated according to the following evaluation criteria.

[0418] Regarding the positive electrode paste of Example 20 and the negative electrode paste of Example 21, these pastes were coated on a current collector (the same aluminum foil as the aluminum foil used in the production of the electrode layer for [the drying time required to form the electrode active material layer]) to produce an electrode layer with an aluminum foil (thickness 80 μm). Except for using the electrode layer produced in this way, T C and T S were measured in the same manner as above, and the deviation of the average film thickness was evaluated.

[0419] -Evaluation Criteria-

[0420] A: Less than 2%

[0421] B: 2% or more and less than 4%

[0422] C: 4% or more and less than 6%

[0423] D: 6% or more and less than 8%

[0424] E: 8% or more and less than 10%

[0425] F: 10% or more

[0426] [Table 3]

[0427]

[0428] From the first aspect of the paste of the present invention, the positive electrode pastes of Comparative Example 1 in which the electrode active material, conductive assistant, and dispersant in the paste do not satisfy all of Formulas (1) to (4), and the positive electrode pastes of Comparative Examples 2 to 5 that satisfy any one of Formulas (1) to (4) all have low dispersion stability, and at least one of the drying time and smoothness of the electrode layer obtained by using them is poor, and the manufacturing adaptability is hardly sufficient. Also, the paste viscosities of the positive electrode pastes of Comparative Examples 3 to 5 are all high, and considering this point, the coatability is also poor.

[0429] In contrast, although the paste viscosities of the positive electrode pastes of Examples 1 to 12 that satisfy all of Formulas (1) to (4) are all low viscosities, the dispersed state can be maintained well even after standing for 72 hours. After the electrode layer is coated using these positive electrode pastes, it can be dried within 60 minutes, and the deviation in film thickness between the center and the ends is also suppressed.

[0430] The same tendency can be seen from the comparison with the negative electrode pastes of Comparative Examples 6 to 10 and Example 13.

[0431] In addition, the same applies to the positive electrode paste and negative electrode paste of the second mode in Examples 20 and 21.

[0432] It can be known that the electrode paste of the present invention can apply a conductive additive with a relatively large specific surface area of 170 m 2 / g or more, and at the same time, can effectively manufacture an electrode layer with high uniformity, and thus has excellent manufacturing adaptability.

[0433] Using each of the obtained electrode pastes, two types of secondary batteries (general non-aqueous electrolyte secondary batteries (abbreviated as non-aqueous electrolyte secondary batteries) and quasi-solid-state secondary batteries) were fabricated, and the energy density and output characteristics of the obtained batteries were evaluated. The following shows the manufacturing method and specific evaluation method of the secondary battery.

[0434] [Fabrication of Non-Aqueous Electrolyte Secondary Battery]

[0435] 1) Preparation of Positive Electrode

[0436] Each of the positive electrode pastes of Comparative Examples 1 to 5 and Examples 1 to 12 was coated on one side of a 12-μm-thick positive electrode current collector (aluminum foil) with a thickness of 120 μm, and dried at 240°C until the dispersion medium was completely volatilized. Then, a pressing process was performed using a roll press at a pressure of 2.7 t, thereby obtaining a sheet-like positive electrode (C-1 to C-17) composed of a positive electrode current collector and a positive electrode active material layer. The thickness of the positive electrode active material layer of this positive electrode was approximately 80 μm.

[0437] 2) Preparation of Negative Electrode

[0438] Each of the negative electrode pastes of Comparative Example 6 and Example 13 was coated on one side of a 12-μm-thick negative electrode current collector (copper foil) with a thickness of 120 μm, and dried at 240°C until the dispersion medium was completely volatilized. Then, a pressing process was performed using a roll press at a pressure of 2 t, thereby obtaining a sheet-like negative electrode (A-1 and A-6) composed of a negative electrode current collector and a negative electrode active material layer. The thickness of the negative electrode active material layer of this negative electrode was approximately 80 μm.

[0439] 3) Preparation of Battery

[0440] The obtained positive electrode and negative electrode were laminated with a separator (thickness: 20 μm) manufactured by W-SCOPE Corporation to form a laminate composed of a positive current collector - positive active material layer - separator - negative active material layer - negative current collector, thereby obtaining an electrode laminate. The combinations of the positive electrode and negative electrode when obtaining the electrode laminate were set as the combinations shown in Table 4. An aluminum sheet and a nickel sheet were respectively welded to the ends of the positive current collector and the negative current collector by ultrasonic welding. A battery assembly was fabricated by accommodating this laminate in a lamination container. After injecting non-aqueous electrolyte 1 in the state where the liquid injection port was open, the liquid injection port was sealed and the housing was hermetically sealed, thereby constructing a lithium-ion secondary battery for evaluation test (ordinary non-aqueous electrolyte secondary battery) (S-1 to S-18).

[0441] [Fabrication of Quasi-Solid-State Secondary Battery]

[0442] The quasi-solid-state secondary battery was fabricated with reference to Japanese Patent Application Laid-Open No. 2016-500465 (Examples 10 and 11). The details are shown below.

[0443] The positive electrode paste of Example 20 was coated on an aluminum foil serving as a positive current collector such that the thickness became 500 μm and the area became 80 cm 2 . Thereby, a positive electrode (C-20) composed of a positive current collector and a positive active material layer was formed.

[0444] Similarly, the negative electrode paste of Example 21 was coated on a copper foil serving as a negative current collector such that the thickness became 500 μm and the area became 85 cm 2 . Thereby, a negative electrode (A-20) composed of a negative current collector and a negative active material layer was formed.

[0445] A separator (thickness: 20 μm) manufactured by W-SCOPE Corporation was cut into an area of 90 cm 2 .

[0446] The separator was laminated on the negative electrode such that the negative electrode was inside the size of the separator, and the separator was laminated thereon such that the positive electrode was inside the size of the negative electrode, thereby fabricating a laminate of negative current collector - negative active material layer (paste) - separator - positive active material layer (paste) - positive current collector. In order to avoid the volatilization of the non-aqueous electrolyte, the fabrication of the laminate was completed within about 1 minute.

[0447] Tab ears were respectively welded by ultrasonic welding on the portions of the aluminum foil of this laminate where the positive electrode paste was not coated and on the portions of the copper foil where the negative electrode paste was not coated. This laminate was wrapped with an aluminum laminate sheet and sealed with a vacuum sealer, thereby fabricating a lithium-ion secondary battery for evaluation test (quasi-solid-state secondary battery) (S-19).

[0448] Volume Energy Density Evaluation Method

[0449] The positive electrode used in the preparation of each of the above secondary batteries was punched into a diameter of 10 mm, and the electrode current collector was taken out from the obtained punched sheet. The thickness of the positive electrode active material layer was measured, and thus the volume of the positive electrode active material layer of the punched sheet was obtained.

[0450] In addition, under Condition 1 of the [Output Characteristics] test described later, charge and discharge were performed to measure the reference discharge capacity (Ah), and the average voltage (V) during discharge was measured. The charge quantity (Wh) was obtained by multiplying the reference discharge capacity (Ah) by the average voltage (V).

[0451] By dividing the charge quantity (Wh) thus obtained by the volume (L) of the positive electrode active material layer obtained above, the volume energy density of the positive electrode active material layer was calculated. The obtained value was applied to the following evaluation criteria for evaluation.

[0452] - Evaluation Criteria -

[0453] A: 400 Wh / L or more

[0454] B: 380 Wh / L or more and less than 400 Wh / L

[0455] C: 350 Wh / L or more and less than 380 Wh / L

[0456] D: 325 Wh / L or more and less than 350 Wh / L

[0457] E: 300 Wh / L or more and less than 325 Wh / L

[0458] F: Less than 300 Wh / L

[0459] [Output Characteristics]

[0460] Under the following conditions, an output characteristics test was performed on the secondary battery fabricated above.

[0461] Specifically, under Condition 1 below, charge and discharge were performed on the secondary battery obtained above to measure the reference discharge capacity. Then, under Condition 2, charge and discharge were performed on the secondary battery obtained above to measure the output evaluation discharge capacity. Based on the obtained reference discharge capacity and output evaluation discharge capacity, the discharge capacity retention rate was calculated using the following formula and applied to the following evaluation criteria for evaluation.

[0462] · Condition 1: Reference discharge capacity

[0463] Constant current (CC) - constant voltage (CV) charging: Current value 25 mA, upper limit voltage 3.9 V, termination current value 2.5 mA

[0464] Constant current (CC) discharge: current value 25 mA, cut-off voltage value 2.0 V

[0465] · Condition 2: Output evaluation discharge capacity

[0466] CC - CV charge: current value 250 mA, upper limit voltage 3.9 V, cut-off current value 25 mA

[0467] CC discharge: current value 1000 mA, cut-off voltage value 2.0 V

[0468] Discharge capacity retention rate (%) = [(Output evaluation discharge capacity) / (Reference discharge capacity)] × 100

[0469] - Evaluation criteria -

[0470] A: 80% or more

[0471] B: 70% or more and less than 80%

[0472] C: 65% or more and less than 70%

[0473] D: 60% or more and less than 65%

[0474] E: 55% or more and less than 60%

[0475] F: Less than 55%

[0476] [Table 4]

[0477] Remark Battery No. Positive Electrode Negative Electrode Energy Density Output Characteristics Comparative Example S-1 C-1 A-1 F F Comparative Example S-2 C-2 A-1 F F Comparative Example S-3 C-3 A-1 E F Comparative Example S-4 C-4 A-1 F F Comparative Example S-5 C-5 A-1 F F Example S-6 C-6 A-1 D E Example S-7 C-7 A-1 D E Example S-8 C-8 A-1 D E Example S-9 C-9 A-1 D D Example S-10 C-10 A-1 D D Example S-11 C-11 A-1 D D Example S-12 C-12 A-1 D C Example S-13 C-13 A-1 D D Example S-14 C-14 A-1 D D Example S-15 C-15 A-1 B C Example S-16 C-16 A-1 A B Example S-17 C-17 A-1 A B Example S-18 C-17 A-6 A A Example S-19 C-20 A-20 A A

[0478] The output characteristics of the non-aqueous electrolyte secondary batteries (S-1 to S-5) having the positive electrodes (C-1 to C-5) manufactured using the positive electrode pastes of Comparative Examples 1 to 5 that do not satisfy at least one of Formulas (1) to (4) are less than 55%, and the volumetric energy density is also less than 325 Wh / L.

[0479] In contrast, the output characteristics of the non-aqueous electrolyte secondary batteries (S-6 to S-18) having the positive electrodes (C-6 to C-17) manufactured using the positive electrode pastes of Examples 1 to 12 that satisfy all of Formulas (1) to (4) are 55% or more, and the volumetric energy density is also 325 Wh / L or more. It can be seen that as long as the electrode paste of the present invention is used, a secondary battery showing excellent battery performance can be obtained.

[0480] In addition, it can be seen that the non-aqueous electrolyte secondary battery (S-18) having the negative electrode (A-6) manufactured using the negative electrode paste of the present invention also has more excellent battery performance.

[0481] Furthermore, it can be understood that a non-aqueous electrolyte secondary battery (S-19) having a positive electrode (C-20) and a negative electrode (A-20) manufactured using the electrode paste of the second method of the present invention also has more excellent battery performance.

[0482] The present invention has been described together with its embodiments, but unless otherwise specified, it is considered that the present invention should not be limited to any details in the description, and should be broadly interpreted without departing from the spirit and scope of the invention shown in the appended claims.

[0483] This application claims the priority of Japanese Patent Application 2022-210786, which was filed in Japan on December 27, 2022, and its content is incorporated herein by reference as part of the description of this specification.

[0484] Reference Signs

[0485] 10 - non-aqueous electrolyte secondary battery, 1 - negative electrode current collector, 2 - negative electrode active material layer, 3 - separator, 4 - positive electrode active material layer, 5 - positive electrode current collector, 6 - working part (light bulb).

Claims

1. A slurry for forming an electrode of a non-aqueous electrolyte secondary battery, which contains an electrode active material, a conductive additive, and a dispersion medium, and satisfies the following formulas (1) to (4). Formula (1): 0 < y - x ≤ 10 Formula (2): 0 ≤ x ≤ 30 Formula (3) S BET ≥ 170, Formula (4): ΔE ≤ 30 In the slurry for forming an electrode, x is the liquid absorption amount (mL) of the dispersion medium in the total amount of every 100 g of the electrode active material and the conductive additive, and can be calculated by the following formula (5). In the slurry for forming an electrode, y is the amount (mL) of the dispersion medium in the total amount of every 100 g of the electrode active material and the conductive additive. S BET is the BET specific surface area (m 2 / g) of the conductive aid, ΔE is the absolute value (mN / m) of the difference between the surface free energy of the dispersion medium and the surface free energy of the conductive additive. Formula (5): x = [Sa × da / 100] + [Sc × dc / 100] Sa is the liquid absorption amount (mL) of the dispersion medium in every 100 g of the electrode active material. da is the proportion (mass %) of the electrode active material in the total amount of the electrode active material and the conductive additive in the slurry for forming an electrode. Sc is the liquid absorption amount (mL) of the dispersion medium in every 100 g of the conductive additive. dc is the proportion (mass %) of the conductive additive in the total amount of the electrode active material and the conductive additive in the slurry for forming an electrode.

2. The slurry for forming an electrode according to claim 1, which contains an electrolyte.

3. The slurry for forming an electrode according to claim 1 or 2, wherein Formula (2) satisfies the following formula (2a). Formula (2a): 0 ≤ x ≤ 21 4. The slurry for forming an electrode according to claim 1 or 2, wherein Formula (4) satisfies the following formula (4a). Formula (4a): ΔE ≤ 25 5. The slurry for forming an electrode according to claim 1 or 2, wherein The surface free energy of the dispersion medium is 20 to 40 mN / m.

6. The slurry for forming an electrode according to claim 1 or 2, wherein The Sa is 10 to 21 mL.

7. The slurry for forming an electrode according to claim 1 or 2, wherein The Sc is 200 to 1700 mL.

8. The slurry for forming an electrode according to claim 1 or 2, wherein The bulk density of the conductive additive is 35 g / L or less.

9. The slurry for forming an electrode according to claim 1 or 2, wherein The conductive additive has been surface-treated.

10. The slurry for forming an electrode according to claim 1 or 2, which contains a dispersant.

11. The slurry for forming an electrode according to claim 1 or 2, wherein The content of the electrode active material is 45 mass % or more.

12. The slurry for forming an electrode according to claim 1 or 2, wherein The content of the solid component exceeds 60 mass %.

13. The slurry for forming an electrode according to claim 1 or 2, wherein The electrode active material is a positive electrode active material.

14. The slurry for forming an electrode according to claim 1 or 2, wherein The proportion da of the electrode active material is 90.00 to 99.99% by mass, and the proportion dc of the conductive additive is 0.01 to 10.00% by mass.

15. A non-aqueous electrolyte secondary battery having a positive electrode, a separator, and a negative electrode in this order, and using the electrode-forming paste according to claim 2 as a positive electrode active material layer and / or a negative electrode active material layer.

16. A method for manufacturing a non-aqueous electrolyte secondary battery, comprising the following steps: Coating the electrode-forming paste according to claim 1 or 2 on an electrode current collector to form an electrode active material layer.

Citation Information

Patent Citations

  • Rechargeable lithium-ion secondary battery

    JP2005108835A

  • Nonaqueous secondary battery

    JP2012185938A

  • Nonaqueous electrolyte and nonaqueous secondary battery

    JP2016201308A

  • Semi-solid electrodes with high speed capability

    JP2016500465A

  • Lithium-ion battery

    JP2017147222A